KRİTİK HASTA BAKIMINDA KAPNOGRAFİNİN ROLÜ - KARCIOĞLU, Özgür (Cerrahpaşa Medical Journal, 2014)
Background. In this article we reviewed the role of endtidal CO2 monitoring the critical care setting as a reliable predictor of tracheal intubation and outcome of patients in emergency setting. Endtidal CO2 concentration level is reported to serve as a discriminating factor between survivors and nonsurvivors in case of cardiopulmonary collapse. Patients with certain levels of endtidal CO2 concentration had significantly lower rates of survival and return of spontaneous circulation. Published data also suggest that initial ETC2 concentration level can be an important predictor of successful endotracheal intubation in lifesaving procedures. More prevalent utilization of capnograph will be a useful adjunct in both detecting endotracheal intubation and also guiding bedside monitoring of cardiopulmonary resuscitation.